Pengembangan Kelompok Peternak Melalui Hibah Sarana Produksi Konsentrat Dan Pendampingan Usaha di Gampong Blang Gurah Kecamatan Kuta Makmur Kabupaten Aceh Utara - Nazaruddin, M.; Nasution, Abdullah Akhyar; Yunanda, Rizki; Ilham, Iromi; Sukmawati, Cut; Kamil, Ade Ikhsan; Huzaifah, Huzaifah; Saragih, Nurul Miftahul Jannah (Universitas Malikussaleh, 2023)
The main problem that has occurred so far is the unsatisfactory livestock productivity. One of the things behind it is the limited availability of animal feed. To get maximum results, one of the important things that must be considered is related to the availability of feed. Thus, community service activities with the theme of concentrate processing are important to be carried out in the farming community of Blang Gurah Gampong, Kuta Makmur District, North Aceh Regency. In 2021, the interdisciplinary lecturer service team has conducted training on making silage, while in 2022, which is a continuation of the previous year, is developing activities for concentrate production and business assistance. The problem experienced by breeders so far is limited knowledge and facilities in processing feed for livestock. So far, what the field team has done is to conduct a survey related to needs during the implementation of activities. While the follow-up agenda of this service is to conduct outreach and training on how to make concentrate feed.